Cocooned: path dependence and the demise of Anderson & Robertson Ltd, Scotland's last silk throwsters. Issue 3 (3rd April 2017) - Yong Ding, Ying; Kininmonth, Kirsten; McKinstry, Sam
Abstract: This study applies the insights of path dependence theory to a Scottish yarn producing firm which existed from 1877 to 1964. Previous longitudinal studies of firms and their strategies have concentrated on larger entities, but the present one tests the relevance of path dependence to smaller firms. The article explains why the firm studied may be seen as an example of path dependence and lock-in, going on to point out why the generally accepted three-stage pathway of reducing organisational choice leading to lock-in appears to fit the case, but that more empirical research in the field would be beneficial. The article highlights in detail the factors which reinforce path dependence and in particular, the role of organisational culture, which has not previously been demonstrated with any precision.